On the Stability of an Equilibrium State of Gyroscopic Coupled Systems - Sosnitskii, S. P. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We investigate the stability of an equilibrium state of gyroscopic coupled conservative systems in the case where the force function does not attain a local maximum in this state. We consider the situation where the gyroscopic coupling is weak with respect to a part of coordinates and strong with respect to the other part.